Mitigating IT Risk of Bank Syariah Indonesia: A Study of Cyber Attack on May 8, 2023 - Rini Fitriani; Rokhmat Subagiyo; Binti Nur Asiyah (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2023)
The rapid development of information technology in Indonesia cannot be overlooked. Technological advancements in all fields must be implemented, including in the world of Islamic banking. Customers need convenience, smoothness, security, and flexibility in digital banking services. Bank Syariah Indonesia (BSI) is the largest Islamic bank in Indonesia. The hashtag "Bank Syariah Indonesia (BSI)" became a trending topic a few days after May 8, 2023. This happened due to the disruption of BSI's information system, causing customers to be unable to conduct banking transactions. Customers were greatly affected by this incident. The purpose of this research is to identify the information technology mitigation efforts carried out by BSI in relation to the incident. This research utilizes a qualitative approach and primary data sources. The primary data used is derived from Twitter, collected from May 4 to May 11, 2023, and reliable websites. The data from Twitter is processed and analyzed using Maxqda 2020 and Gephi version 0.9.6 software for Windows 10 64-bit. The conclusion of this research is that BSI's information technology mitigation efforts are still slow.